Pengaruh Olah Raga Pencak Silat Terhadap Mental Emosional - Yudaparmita, Gusti Ngurah Arya (STAHN Mpu Kuturan Singaraja, 2023)
This research aims to determine the influence of pencak silat sports on the emotions of PGSD students at STAHN Mpu Kuturan Sigaraja. Emotional is a branch of psychology that discusses a person's emotional turmoil in responding to things. These feelings include sadness, happiness, disappointment, fear, worry, and others. Everyone will definitely feel all these feelings, but if it is said that they have an emotional soul, someone is expressing emotions excessively or can be called an emotional mind. Pencak Silat is a sport that uses a person's dexterity, strength and balance against other players. In terms of emotions, students who have activities and a level of mastery that is more than high school or elementary school will experience a very significant spike in adaptation. In the sport of pencak silat, it has a strong enough influence to be able to control a person's mental and emotional state, so that when doing something there is no excessive emotion.